Aid and the Dutch Disease in Low-Income Countries : Informed Diagnoses for Prudent Prognoses - Nkusu, Mwanza (IMF Working Papers; Working Paper ;, 2004)
This paper demonstrates that the Dutch disease need not materialize in low-income countries that can draw on their idle productive capacity to satisfy the aid-induced increased demand. Diagnoses on, and prognoses for, the Dutch disease should take into account country-specific circumstances to avoid ill-advised policies. The paper emphasizes that using public resources inefficiently can be more painful than real exchange rate appreciations, which may not necessarily embody the Dutch disease.